A multicenter randomized trials to compare the bioequivalence and safety of a generic doxorubicin hydrochloride liposome injection with Caelyx ® in advanced breast cancer - Li, Yinjuan; Qi, Lu; Wang, Yu; Li, Yan; Lei, Chunpu; Zhang, Yingjuan; Cheng, Xiaoqiang; Liu, Ju; Bai, HaiHong; Zhao, Xia; Lv, Shuzhen; Xiong, Bingjun; et al. (Frontiers in Oncology, 2022)
Purpose To compare the pharmacokinetic (PK) bioequivalence (BE) and safety of a generic pegylated liposomal doxorubicin (PLD) formulation with the reference product Caelyx®. Methods A multicenter, single-dose, open-label, randomized，two-way crossover study was conducted in patients with breast cancer. For each period, the patients were administered with the test or the reference PLD intravenously at a dose of 50 mg/m2. Cmax, AUC0−t and AUC0−∞ for free, and encapsulated doxorubicin (doxorubicin) and partial AUC (AUC0−48h, AUC48h−t) for encapsulated doxorubicin were evaluated in 17 blood samples taken predose, and increasing time intervals over the following 14 days in each period. A washout period of 28-35 days was observed before crossing over.